The Associations of Lymphocyte Ratio and Neutrophil Ratio on Liver Dysfunction in COVID-19 Patients - Liu, Fang; Liu, Hong; Yu, Wen-Yan; Liu, Zhan; Zhang, Xia; Wang, Yi; Miao, Liang-Bin; Li, Zhao-Yi; Huang, Jin-Song; Bao, Jian-Feng (Frontiers in Immunology, 2021)
Data on the impact of lymphocytes and neutrophils on the incidence of liver dysfunction in COVID-19 patients are limited. This study aimed to investigate the lateral and longitudinal associations of lymphocyte ratio (LR) and neutrophil ratio (NR) on liver dysfunction in COVID-19 patients. We tested 1409 blood samples from 245 COVID-19 patients in China between January 2020 and June 2021. The lateral U-shaped relationships, determined by smooth curve fitting and piecewise-linear mixed effect model, were observed between LR, NR and AST and the incidence of AST-linked liver dysfunction, with the threshold cutoffs of 26.1 and 62.0, respectively. Over the 1409 tests, the LR ≤26.1 and NR ≥62.0 related to the occurrence of mild liver dysfunction (HR: 1.36; 95% CI: 1.01, 1.82), moderate liver dysfunction (HR: 1.37; 95% CI: 1.01, 1.85), and severe liver dysfunction (HR: 1.72; 95% CI: 1.02, 2.90). For the patients with pre-existing AST ≥35U/L, baseline LR ≤26.1 and NR ≥62.0 (b.LLCHN) group had a full adjusted 8.85-fold, 7.88-fold, and 5.97-fold increased risk of mild and moderate liver dysfunction after hospitalized of 3 days, 6 days, and 9 days compared to baseline LR >26.1 and NR <62.0 (b.normal) group. Severe liver dysfunction only presents significant differences after being adjusted for age, sex, and BMI. Consistently, Kaplan–Meier analyses showed that b.LLCHN reflects a better predictive value for different subsequent magnitude liver dysfunction after admission of 3 days and 6 days. To improve liver function in patients with pre-existing AST ≥35U/L, future management strategies should pay more attention to baseline LR ≤26.1 and NR ≥62.0 patients.